Fabrication and characterisation of novel algin incorporated bioactive-glass 58S calcium-silicate-based root canal sealer - Galvin Sim Siang Lin; Daniel Hong Heng Sim; Norhayati Luddin; Josephine Chang Hui Lai; Huwaina Abd Ghani; Tahir Yusuf Noorani (Elsevier, 2023)
Background/purpose: The usage of bioceramic-based root canal sealers has escalated over the years due to their excellent properties. The present study aimed to fabricate a novel algin incorporated bioactive glass 58S calcium-silicate (Bio-G) sealer and characterise its surface microstructure and chemical compositions in comparison to commercially available bioceramic sealers (BioRoot RCS and iRoot SP). Materials and methods: The powder form of experimental Bio-G sealer consisted of synthesised BG 58S particle, calcium silicate, zirconia dioxide, calcium carbonate and alginic acid powder as binder. The liquid composed of 5% calcium chloride solution. Five standardised disc specimens were prepared for each sealer group according to the manufacturer's instructions. Subsequently, sealer disc-specimens were placed in an incubator at 37 °C, 95% relative humidity for 72 h to allow setting prior to testing under scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), Fourier transformed infrared spectroscopy (FTIR) and X-ray diffraction (XRD). Results: Experimental Bio-G sealer revealed irregular micro-sized particles ranging from 0.5 μm to 105 μm aggregated in clusters comparable to those of BioRoot RCS and iRoot SP. EDS microanalysis showed that Bio-G had high content of oxygen, silicon, and calcium, with the presence of aluminium and chloride similar to BioRoot RCS. Meanwhile, the FTIR and XRD findings suggested that all sealers predominantly contained calcium silicate hydrate, calcium carbonate, and zirconium dioxide, while calcium aluminium silicate oxide was detected in Bio-G. Conclusion: The present novel Bio-G sealer demonstrated desirable particle size distribution and acceptable degree of purity. Future studies are warranted to explore its properties and clinical application.